Challenges for Foundation Phase Teachers in Interacting with Parents during the COVID-19 Pandemic: A Case Study of Mangaung Primary Schools, South Africa - Grobler, Annemie (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2022)
The sociocultural theory of learning acknowledges parents as integral role players in the process of their children’s learning. As in many other parts of the world, when South African schools moved to remote online learning due to the COVID-19 pandemic, teachers became increasingly dependent on the agency of parents. Using an interpretivist lens and a qualitative approach, this study probes the experiences of Foundation Phase teachers in South Africa’s Mangaung Municipality in their interaction with parents in 2020, during the pandemic lockdowns. The findings point to the following challenges during the pandemic, as perceived by the teachers: difficulty in communicating with parents; difficulty in working with parents to support learning; and insufficient parental commitment. The findings also point to shortfalls in respect of three dynamics—collaboration, feedback, and trust—as being central to the perceived challenges. The study concludes with a call for improved relations between Foundation Phase parents in teachers, regardless of whether the teaching and learning are occurring remotely or in-person, in order to optimise the sociocultural dynamics at play in children’s schooling.